Complement C4, Infections, and Autoimmune Diseases - Wang, Hongbin; Liu, Mengyao (Frontiers in Immunology, 2021)
Complement C4, a key molecule in the complement system that is one of chief constituents of innate immunity for immediate recognition and elimination of invading microbes, plays an essential role for the functions of both classical (CP) and lectin (LP) complement pathways. Complement C4 is the most polymorphic protein in complement system. A plethora of research data demonstrated that individuals with C4 deficiency are prone to microbial infections and autoimmune disorders. In this review, we will discuss the diversity of complement C4 proteins and its genetic structures. In addition, the current development of the regulation of complement C4 activation and its activation derivatives will be reviewed. Moreover, the review will provide the updates on the molecule interactions of complement C4 under the circumstances of bacterial and viral infections, as well as autoimmune diseases. Lastly, more evidence will be presented to support the paradigm that links microbial infections and autoimmune disorders under the condition of the deficiency of complement C4. We provide such an updated overview that would shed light on current research of complement C4. The newly identified targets of molecular interaction will not only lead to novel hypotheses on the study of complement C4, but also assist to propose new strategies for targeting microbial infections as well as autoimmune disorders.